2018
DOI: 10.2147/cmar.s178213
|View full text |Cite|
|
Sign up to set email alerts
|

CircRNA CDR1as/miR-7 signals promote tumor growth of osteosarcoma with a potential therapeutic and diagnostic value

Abstract: BackgroundThe circular RNA (circRNA) antisense to the cerebellar degeneration-related protein 1 transcript (CDR1as)/micro RNA-7(miR-7) signal axis has been investigated in many diseases via regulation of the target genes of miR-7, which participates in the carcinogenesis and metastasis. However, the clinical role and function of CDR1as/miR-7 pathway in osteosarcoma (OS) remain to be identified.Materials and methodsNoncancerous bone tissues (n=18) and OS tissues (n=38) were used to determine the expressions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 21 publications
1
84
0
Order By: Relevance
“…Furthermore, the circRNA CDR1as/miR-7 pathway regulates the EMT phenotype. Furthermore, a miR-7 inhibitor can enhance the metastatic ability of HCC and OS cells [123,124].…”
Section: Other Pathways Related To Circrnasmentioning
confidence: 99%
“…Furthermore, the circRNA CDR1as/miR-7 pathway regulates the EMT phenotype. Furthermore, a miR-7 inhibitor can enhance the metastatic ability of HCC and OS cells [123,124].…”
Section: Other Pathways Related To Circrnasmentioning
confidence: 99%
“…Moreover, 22 studies were further eliminated with a variety of reasons, including ve studies not related to circRNAs or osteosarcoma, six studies did not report outcomes, two reviews and case reports, four animal studies, and ve lack of extractable data. Finally, 26 studies comprising 1,652 osteosarcoma cases were enrolled in this quantitative study, with 18 on clinicopathological features, ten on diagnosis [13,18,19,21,24,[30][31][32][33][34] [12,14,18,19,[32][33][34][36][37][38][39][40], whereas other two studies on downregulated circRNAs applying ≥ 18 or < 18 years old to separate enrolled patients [13,30]. In consideration of the consistency, only these studies with common cut-off value were included in the following meta-analysis with regard to patients' age.…”
Section: Characteristics Of the Enrolled Studiesmentioning
confidence: 99%
“…The duration for follow-up ranged from 40 to 125. For diagnostic assay, ten studies with data on sensitivity, speci city and AUC [13,18,19,21,24,[30][31][32][33][34]. The quality of studies was evaluated by QUADAS II and NOS scores.…”
Section: Characteristics Of the Enrolled Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Song et al found that hsa_circ_0001564 acts as a miR-29c-3p sponge to cause tumourigenesis and may serve as a potential biomarker for OS [16]. In addition, a related study found that circRNA CDR1as/miR-7 signalling promotes tumour growth in OS, with potential therapeutic and diagnostic value [17]. These studies indicate that cir-cRNAs play an important role in the development and progression of OS.…”
Section: Introductionmentioning
confidence: 99%